Encyclopedia of food and culture. Volume 1 / Solomon H Katz; William Woys Weaver - Katz, Solomon H
This stunning source explores the nutritional and cultural impact of food, with articles written by anthropologists, chefs, food historians, nutritionists, agronomists, food stylists, and other food researches. The well-written and informative entries cover the history of regional cuisines, major festivals and feasts, and general subjects that examine the cultural, sociological, and psychological perspectives of food. Encyclopedia of Food and Culture will be a classic for years to come."--"The Top 20 Reference Titles of the Year," American Libraries, May 2004. This Dartmouth Medal winning 3 volume set presents 600 articles on food and its place in human culture and society, covering everything from agronomy to zucchini. Students, academics and general researchers will find entries on everything from food preparation, distribution and storage to holidays and festivals, nutrition and health, and cultures and cuisines. The Encyclopediaʼs multidisciplinary articles range from 250 to 10,000 words each and are supplemented by 450 photographs and illustrations, sidebars, recipes, menus, timelines and a comprehensive index. Systematic outline of contents: Foods: staple foods, Foods: cooked, processed & prepared, Icon foods and superfoods, Beverages, Food production, Food storage, Food Distribution, Food preparation, processing & disposal, Food consumption, The premodern world, Regions, cultures & groups, Human evolution, Nutrition, health & food sciences, Biological basis of nutrition & digestion, Psychology of eating, Diet, Constituents of food, Conditions, disorders & diseases, Hunger, Policy, Food & society, Religion, Feasts, festivals & fasts, Food as Symbol & commodity, Writing about food, Study of food, Biographies.